L’amicizia con Gladio Gemma negli anni del nostro insegnamento a Modena (Stato, Chiese e pluralismo confessionale, 2022)
The friendship with Gladio Gemma in the years of ours teaching in the University of ModenaSOMMARIO: 1. Premessa - 2. I fatti della politica e l’ambizione di contribuire alle esigenze di armonizzazione costituzionale e allo sviluppo della vita democratica in Italia - 3. Il concilio Vaticano Il e le trasformazioni della società italiana negli anni sessanta - 4. Il dibattito culturale e politico sulla riforma della legislazione ecclesiastica.ABSTRACT: Individuals and experiences that, in the years between 1962 and 1970, had an important influence on the civic and political growth of the author and Gladio Gemma. New focus was given to the issue of relations between the State and the Catholic Church in the late fifties. The Second Vatican Council from 1962 to 1965 and the transformation of Italian society in the 1960s. Tendencies in the jurisprudence on the theme of relations between the state and religious confessions. The cultural and political debate on the reform of ecclesiastical legislation.